Empirical Study of the Linkage between Insurance Determinants and Economic Growth: Evidence from Algeria over the Period 1990-2019 - aksa ahlem; hallam zouaouia (Journal of Excellence for Economics and Management Research, 2021)
The study investigates the relationship between insurance, bank credit, employment, trade openness and economic growth in Algerian economy. The paper employed Vector Error Correction Model (VECM) and annual data from 1990 to 2019.The results from Johansen integration test underpins for the existence of long run relationship among the purported variables. Granger Causality test exhibits unidirectional causality running from bank credit and employment to the economic growth in Algeria. The study advocates for the acceleration of insurance products in tandem with enhancing the ambit of trade openness and bank credits for stimulating the economic growth in Algeria.